SCHOOL PARTNERSHIP’S PERCEPTION TOWARD VIRTUAL PRE-SERVICE EFL TEACHER ( PLP ) PROGRAMME DURING PANDEMIC COVID 19 - Dian Adiarti; Mia Fitria Agustina (Universitas Muhammadiyah Semarang, 2021)
Pre service EFL Teacher Training is obligedly conducted for the seventh semester by students of Teaching Department to enchanche their teaching practice at some schools partnership. This programme is one of the requirements for teacher candidate before graduating from university. In pandemic Covid 19, this programme had to be conducted virtually at some schools partnerships, if not, they had to repeat this programme in the next semester. This, created positive and negative opinion and perception for teachers as internship students mentor, especially for schools partnership. Some various school parthnership’s opinions triggered the writter to investigate and analize the evaluation of this programme. This research is aimed to collect and analize the data of school partneship’s opinion toward virtual Pre Service teacher training. The evaluation of this programme covered students’teaching performance, basic studnts’s competencies; cognitive, affective, psikomotoric, social affective, and educative traits. The data were collected from the interveiw of some PIC’S schools partnership especially teachers, headmasteres who directly evaluated the students’ virtual teaching performance. The qualitative research as the macro research. The purposive sample is used to collect the data through interviews and the researcher sent some questioraires. The findings showed that virtual students internship resulted positive and negative perceptions for school partnerships. Headmasters/PIC of students Internship and mentor chose the average of positive argument and it resulted 88,1% while for the average of negative statement it resulted 90,1 %. This means that negative perception is the findings. Negative percetion might appear because the school parnership doubt for not fulfilling the faculty’s demand. Some elements were difficult to be evaluated but school partnership got benefits from this situation.